PERANCANGAN DAN PENGEMBANGAN PRODUK AUTOMATIC IRRIGATION SYSTEM DENGAN MENGGUNAKAN SENSOR KELEMBAPAN TANAH - Ardianto, Dwi arizky; Khairunnisa, Serlia; Lukito, Suryo Tondo; Naufaldrin, Rifqi Ramadhan; Azzahra Riyana, Tharra; Parwati, Niken (LPPM Universitas Bina Bangsa, 2024)
Agriculture is an essential sector in the global economy that plays a key role in meeting the world's food needs. However, one of the main challenges faced by farmers is providing an adequate water supply for their crops. Inconsistent and unscheduled water availability can have negative impacts on plant growth, productivity, and harvest yields. In an effort to address this challenge, automatic irrigation systems have been developed. An automatic irrigation system is a system that automatically provides water to plants based on measured and controlled water requirements using smart sensors and controls. This system helps ensure that plants receive the right amount of water they need, at the right time, and in the right place. Product development is an activity carried out to improve a product towards providing greater benefits and satisfaction. Based on the data collection and processing related to the design and development of the Automatic Irrigation System (ACTION System), it can be concluded that the designed and developed product meets the needs and desires of consumers, as evidenced by the obtained questionnaire results. The Automatic Irrigation System (ACTION System) has an additional innovation: it can automatically water dry soil due to its moisture sensor.